Naive Bayes Based QoS for Wireless Sensor Networks - Beula Darling, T; Suganthi, G (International Journal of Computer Sciences and Engineering, 2019)
Sensor networks is widely used in real-time applications that have made emergent of Quality of Service (QoS) based communication schemes. Recently QoS in sensor network becoming an interesting topic among the research community. This paper proposes a Naïve Bayes based QoS mechanism, which is suitable for both real-time and non-real-time applications. The proposed mechanism achieves the desired QoS by selecting the neighboring nodes in a way to meet the required QoS. Performance of the scheme is evaluated through simulations. The results provide insights on the performance of the system based on different evaluation metrics such as end-to-end delay, packet delivery ratio and the node failure probabilities. The results demonstrate that the scheme is able to outperform the compared mechanisms such as Multi-constraint Multi-Path (MCMP) routing protocol and energy efficient QoS aware routing protocol (EQSR) using both real time traffic (EQSR-RT) and non-real time traffic(EQSR-NRT).